(A Study of Isothrm Sorption, Temperature and Number of Layers on the K Value of Coconut Fiber) - Guring Pohan, H; Yang Setiawan, Yang (Balai Besar Industri Agro, 2000)
The rsearch of coconut fiber has been carried out to determined isotherm sorption and rate of weight decrease during drying. Isotherm sorption was done by adjusting room water activity which are 10%, 35%, 65%, 90% and 99%. The calculating data of research show linier regression with equation Y= 0.336156 X - 0.02038, R2= 0.9743, C=15.49 and m0=3.16. decreasing weinght of fiber was studied to find out the effect of amount of layer (1, 3 and 5 layers) and drying temperature (50 C, 60 C and 70 C). The result show that the temperature has no significant effect while amount of layer very significant to the dryness of fiber. The highest k value was found in the 1 layer treatment between 0.47912 - 0.85270, while the lowest k value found in the 5 layers treatment those are vary between 0.16770-.19793.